Efficacy and safety of first-line immunotherapy plus chemotherapy in treating patients with extensive-stage small cell lung cancer: a Bayesian network meta-analysis - Zhang, Tianming; Li, Wenjun; Diwu, Danbei; Chen, Lijun; Chen, Xi; Wang, Hong (Frontiers in Immunology, 2023)
Background: Despite numerous immunotherapy and chemotherapy regimens available for patients with extensive-stage small cell lung cancer, it remains opaque which regimen is the most effective and safest, the relative studies comparing those regimens were modicum. Objective: To investigated the efficacy and safety of first-line therapy immunotherapy combinations with chemotherapy for patients with extensive-stage small cell lung cancer,In addition, for the first time, comparisons among the first-line systemic regimens on OS and PFS in ES-SCLC by each time node. Methods: Databases including PubMed, Embase, Cochrane Library, Scopus, Google Scholars, ClinicalTrials.gov, and major international conferences were searched for randomized controlled trials (RCTs) regarding to comparing immunotherapy combinations with chemotherapy as first-line treatments for patients with advanced ES-SCLC from inception to November 1st. Hazard ratios (HRs) and odds ratios (ORs) were generated for dichotomous variants by RStudio 4.2.1. The outcomes comprised overall survival (OS), progression free survival (PFS), objective response rate (ORR), and adverse events of grade 3 or higher (Grade ≥ 3 AEs). Results: Eventually a total of 9 RCTs reporting 4352 individuals with 9 regimens were enrolled. The regimens were ipilimumabnu (Ipi), atezolizumab (Atez), durvalumab plus tremelimumab (Durv-Trem), durvalumab (Durv), pembrolizumab (Pemb), adebrelimab (Adeb), serplulimab (Serp), atezolizumab plus tiragolumab (Atez-Tira), nivolumab (Nivo). With regard to OS, serplulimab (HR= 0.63, 95%CI: 0.49 to 0.81) were found to yield best OS benefit when compared with chemotherapy. Meantime, serplulimab had the highest probability (46.11%) for better OS. Furthermore, compared with chemotherapy, serplulimab significantly increased the OS rate from the 6th to 21st months. With regard to PFS, serplulimab (HR= 0.47, 95%CI: 0.38 to 0.59) were found to yield best PFS benefit when compared with chemotherapy. Simultaneously, serplulimab had the highest probability (94.48%) for better PFS. Serplulimab was also the long-lasting first-echelon regimen both in OS and PFS from a longitudinal perspective. In addition, there was no significant difference among the various treatment options for ORR and grade ≥3 AEs. Conclusion: Considering OS, PFS, ORR, and safety profiles, serplulimab with chemotherapy should be recommended as the best therapy for patients with ES-SCLC. Certainly, more head-to-head studies are needed to confirm those findings.